Battery Recharging Issue for a Two-Power-Level Flywheel System. (27th July 2010) - Gonçalves de Oliveira, Janaína; Bernhoff, Hans
Abstract : A novel battery recharging system for an all-electric driveline comprising a flywheel with a permanent magnet double wound synchronous machine (motor/generator) is presented. The double winding enables two voltage levels and two different power levels. This topology supersedes other all-electric drivelines. The battery operates in a low-power regime supplying the average power whereas the flywheel delivers and absorbs power peaks, which are up to a higher order of magnitude. The topology presents new challenges for the power conversion system, which is the focus of this investigation. The main challenge is the control of the power flow to the battery when the vehicle is parked despite the decay of the flywheel machine voltage; which is dependent on its charge state, that is, rotational speed. The design and simulation of an unidirectional DC/DC buck/boost converter for a variable rotational speed flywheel is presented. Conventional power electronic converters are used in a new application, which can maintain a constant current or voltage on the battery side. Successful PI current control has been implemented and simulated, together with the complete closed loop system.